Contrasting Carboannulation Involving δ-Acetoxy Allenoate as a Four-Carbon Synthon Using DABCO and DMAP: Access to Spiro-carbocyclic and m-Teraryl Scaffolds - Kumar, A. Sanjeeva; Chauhan, Sachin; Swamy, K. C. Kumara (Organic letters, 2021)
Spiro-annulation involving delta-acetoxy allenoate and alkyl benzoisothiazole dioxide (N-sulfonyl ketimine) triggered by DABCO/MeCO2H combination leads to an essentially single diastereomer via chemo- and regiospecific [4 + 2]-carboannulation and a new hydroxyl group is introduced. In contrast, DMAP-catalyzed benzannulation using the same reactants affords unsymmetrical m-teraryls via Mannich coupling, sequential proton transfers, and C-N bond cleavage. Here, delta-acetoxy allenoate serves as a 4C-synthon and the carboannulation is completely base dependent and mutually exclusive.